ENDORPHIN MASSAGE AS A COMPLEMENTARY INTERVENTION TO REDUCE ANXIETY AMONG EARLY POSTPARTUM MOTHERS - Marleni Leni; Meliawati (Jurnal Smart Kebidanan, 2026)
Postpartum anxiety is a common psychological problem experienced by mothers during the early postpartum period and may adversely affect maternal well-being, mother–infant bonding, and breastfeeding outcomes. This study aimed to determine the effectiveness of endorphin massage as a complementary intervention in reducing anxiety among early postpartum mothers. A quantitative study using a quasi-experimental pretest–posttest control group design was conducted among 70 postpartum mothers (1–7 days postpartum) in the working area of Kelapa Public Health Center, West Bangka Regency, Indonesia. Participants were selected using accidental sampling and allocated into an intervention group (n = 35) and a control group (n = 35). Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). The intervention group received endorphin massage once daily for three consecutive days, while the control group received routine postpartum care. The mean anxiety score in the intervention group decreased from 32.0 before the intervention to 20.3 after the intervention, whereas the control group showed only a slight decrease from 30.4 to 30.0. Wilcoxon test results indicated a significant reduction in anxiety levels in the intervention group (p < 0.001). Furthermore, the Mann–Whitney test demonstrated a significant difference in posttest anxiety scores between the intervention and control groups (p < 0.001). Endorphin massage was found to be effective in reducing anxiety among early postpartum mothers. This intervention may be recommended as a safe, non-pharmacological complementary therapy to enhance psychological well-being during the postpartum period.